On the Art of Modeling - Morris, William T. (Management Science, 1967)
The problem of teaching or developing creative modeling ability is considered in the light of three basic hypotheses concerning the processes of enrichment (elaboration of very simple models), association (analogy with previously developed structures), and alternating attention to different aspects of the task. Based on these hypotheses, specific steps are presented which have been developed to help individuals acquire modeling skills. The steps are illustrated by means of an example. Other sources of modeling ability are also suggested. The discussion focuses on specific hypotheses concerning the differences between the teaching of models and the teaching of modeling.